2012
DOI: 10.1111/j.1467-8624.2012.01864.x
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Experiences of Discrimination and African American Adolescents’ Psychological Health Over Time

Abstract: The present study examined the effect of caregivers' experiences of racial discrimination on their adolescent children's psychological functioning among a sample of 264 African American dyads. Potential relations between caregiver discrimination experiences and a number of indicators of adolescents' (aged 12-17) psychological functioning over time were examined. It was found that caregiver discrimination experiences were positively related to adolescents' symptoms of depression and negatively related to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 42 publications
(61 reference statements)
4
59
3
1
Order By: Relevance
“…Consistent with previous research we found that boys are at a greater risk than girls for engaging in disruptive behaviors (Brennan & Shaw, ; Leadbeater et al., ). However, and also consistent with previous research (Ford et al., ), in the context of PC experiences of discrimination, we found that boys and girls were of equal likelihood to engage in disruptive behaviors. Therefore, the present study suggests that there is not a differential response to parental discrimination by gender, such that boys and girls are at equal risk for engaging in disruptive behaviors in response to caregiver discrimination.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous research we found that boys are at a greater risk than girls for engaging in disruptive behaviors (Brennan & Shaw, ; Leadbeater et al., ). However, and also consistent with previous research (Ford et al., ), in the context of PC experiences of discrimination, we found that boys and girls were of equal likelihood to engage in disruptive behaviors. Therefore, the present study suggests that there is not a differential response to parental discrimination by gender, such that boys and girls are at equal risk for engaging in disruptive behaviors in response to caregiver discrimination.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, discrimination, whether experienced personally or vicariously through caregivers, may create a stressful environment, which in turn may play a key role in the development of children's disruptive behavior. Ford, Hurd, Jagers, and Sellers (2013) suggested that the quality of the relationship between caregivers and children might affect the extent to which caregiver discrimination relates to child outcomes. High rates of parent-child conflict are associated with more externalizing symptoms (Burt, McGue, Iacono, & Krueger, 2006;Klahr, McGue, Iacono, & Burt, 2011).…”
Section: S T I C H W ö R T E Rmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, children fare worse when their parents experience workplace discrimination. When parents of African American early adolescents experienced workplace discrimination, their children reported more substance use and psychological distress (Ford, Hurd, Jagers, & Sellers, ; Gibbons, Gerrard, Cleveland, Wills, & Brody, ). Parental workplace discrimination was related to lower nonverbal ability scores, among Black children living in the United Kingdom (Kelly, Becares, & Nazroo, ).…”
Section: Theoretical Linkages Between Parents’ Workplace Experiences mentioning
confidence: 99%